The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1590/1980-5918.030.003.ao13
|View full text |Cite
|
Sign up to set email alerts
|

Postural alignment of patients with Chronic Obstructive Pulmonary Disease

Abstract: Introduction: In chronic obstructive pulmonary disease (COPD), airflow resistance impairs respiratory mechanics that may compromise postural alignment. There is a lack of studies that have investigated compromised postures and their possible associations with pulmonary function. Objectives: To compare the postural alignment of COPD patients with apparently healthy individuals; To correlate pulmonary function with postural alignment in the COPD group. Methods: 20 COPD patients and 20 apparently healthy individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
4
1
1
Order By: Relevance
“…Furthermore, Lee et al 9 reported more thoracic kyphotic values in patients with COPD than healthy individuals 51.8 vs. 39.1 respectively. In our study, patients with emphysema demonstrated more thoracic kyphotic changes than reported by Gonçalves et al 7 in people with COPD. These changes could be due to the fact that the individuals recruited for our study were more severely impaired.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Furthermore, Lee et al 9 reported more thoracic kyphotic values in patients with COPD than healthy individuals 51.8 vs. 39.1 respectively. In our study, patients with emphysema demonstrated more thoracic kyphotic changes than reported by Gonçalves et al 7 in people with COPD. These changes could be due to the fact that the individuals recruited for our study were more severely impaired.…”
Section: Discussionsupporting
confidence: 50%
“…Garreau de Loubresse and Wolff 23 have observed that thoracic kyphotic angle is closely associated with lung function. Previous studies 7,11 demonstrated that patients with COPD have exaggerated kyphotic posture than healthy controls. Furthermore, Lee et al 9 reported more thoracic kyphotic values in patients with COPD than healthy individuals 51.8 vs. 39.1 respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The use of photogrammetry for postural evaluation is already well established in scientific research and clinical practice [13][14][15][16]. In recent years, this resource has also been used for rib cage evaluation [17][18] and increasingly for the assessment of thoracoabdominal mobility in children [19], newborns [20] and adults [21], in populations ranging from athletes [21] to individuals with respiratory diseases [22][23]. However, there has been no other study using this technique to assess thoracoabdominal mobility in children with CF.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusion: Our study showed in CF a reduction in pulmonary function, strong positive correlation between APMUC and pulmonary function, high prevalence of kyphoscoliosis and strong negative correlation between AHA and pulmonary function. Resultados: As seguintes variáveis espirométricas apresentaram-se reduzidas em relação ao previsto: VEF 1, VEF 1 / FVC, PFE e FEF 25-75%. Na avaliação postural, foram observadas alterações no alinhamento horizontal da cabeça (AHC,2,71 ± 2,23); alinhamento horizontal acrômios (AHA, 1,33 ± 1,35); alinhamento horizontal espinhas ilíacas ântero-superiores (AHEIAS, 1,11 ± 0,89); ângulo entre dois acrômios e duas espinhas ilíacas ântero-superiores (AEDAEDEIAS, 0,89º± 0,39); assimetria horizontal de escápula em relação a T3 (AHERT3, 16,95% ± 12,03); assimetria da projeção do centro de gravidade na base de sustentação no plano frontal (11,45 ± 8,10%) e sagital (48,98±18,55%). Foi encontrada correlação positiva forte entre função pulmonar e mobilidade toracoabdominal nas variáveis: distâncias anteroposterior do tórax superior (DAPTS) e FVC (r = 0,818; p = 0,024); DAPTS e VEF 1 (r = 0,874; p = 0,010); DAPTS e FEF 25-75% (r = 0,797; p = 0,032).…”
unclassified